Induction immunosuppression and post-transplant diabetes mellitus: a propensity-matched cohort study - Gupta, Suruchi K.; Mostofsky, Elizabeth; Motiwala, Shweta R.; Hage, Ali; Mittleman, Murray A. (Frontiers in Endocrinology, 2023)
Introduction: Post-transplant diabetes mellitus (PTDM) is a common complication among cardiac transplant recipients, causing diabetes-related complications and death.While certain maintenance immunosuppressive drugs increase PTDM risk, it is unclear whether induction immunosuppression can do the same. Therefore, we evaluated whether induction immunosuppression with IL-2 receptor antagonists, polyclonal antilymphocyte antibodies, or Alemtuzumab given in the peri-transplant period is associated with PTDM.Methods: We used the Scientific Registry of Transplant Recipients database to conduct a cohort study of US adults who received cardiac transplants between January 2008-December 2018. We excluded patients with prior or multiple organ transplants and those with a history of diabetes, resulting in 17,142 recipients. We created propensitymatched cohorts (n=7,412) using predictors of induction immunosuppression and examined the association between post-transplant diabetes and induction immunosuppression by estimating hazard ratios using Cox proportional-hazards models.Results: In the propensity-matched cohort, the average age was 52.5 (SD=13.2) years, 28.7% were female and 3,706 received induction immunosuppression. There were 867 incident cases of PTDM during 26,710 person-years of follow-up (32.5 cases/1,000 person-years). There was no association between induction immunosuppression and post-transplant diabetes (Hazard Ratio= 1.04, 95% confidence interval 0.91 -1.19).Similarly, no associations were observed for each class of induction immunosuppression agents and post-transplant diabetes.Conclusions: The use of contemporary induction immunosuppression in cardiac transplant patients was not associated with post-transplant diabetes.